Individuals' Interest in Preventing Everyday Accidents and Crises: A Swedish Explorative Study of the Importance of Motivation - Wall, Erika (Human Technology, 2014)
This explorative study presents an empirical examination of the connection between motivation and the measures individuals take to prevent everyday accidents and prepare for crises. Positional factors (age and gender) and situational factors (education, size of locality, and household composition) are included because the literature highlights their importance. The study used data gathered in a 2010/2011 poll of randomly selected Swedish residents aged 16–75 (N = 2000; 44.8% response rate). A factor analysis reduced the theoretical model for situational motivation (Guay, Vallerand, & Blanchard, 2000) from four to two dimensions: motivation and amotivation. Subsequent regression analyses statistically confirmed the connection between motivation or amotivation and the extent to which individuals pursue preventative and preparedness measures, even when accounting for positional and situational factors. These findings underscore the need for continued studies of individuals' incentives to prevent accidents and prepare for crises and for the study of the nuances of (situational) motivation and preventive/preparedness measures.